Sociological impact in public toilet design: case study of KAED Malay Heritage Living Lab - Abdul Rahman, Julaila; Dzulkiflee, Wan Nur Aisyah; Abdullah, Fazidah; Alias, Nur Ulfah Awatif Umairah; Ayob, Mohd Fairullazi; Che Haron, Roziha; Syed kamaruzaman, Sharifah Tahirah; Mohyin, Nur Affah (IIUM Press, 2025)
Human interaction in public spaces is influenced by both environment and culture. Public toilets, however, often fall short in meeting user needs due to poor facilities and lack of proper amenities. In the Malay cultural context, Adat plays an important role in shaping social behaviour and shared practices ,which can guide more context-sensitive design. This project explores the sociological and cultural dimensions of public toilet design with a focus on human factors. The objectives are: (1) to identify design criteria for public toilets, (2) to examine contextual impacts on user behaviour, and(3) todevelopa3Dmodel for restroom of Rumah Kutai.Thestudyemploysliteraturereview,casestudies,andsiteobservationswithintheKAEDMalayHeritageLivingLab, IIUM. Findings are expected to highlight culturally rooted design criteria and demonstrate how traditional values can be integrated with functional requirements to create inclusive, responsive, and sustainable public toilet facilities.